2010
DOI: 10.1111/j.1542-474x.2010.00375.x
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Pulse Oximetry in the Diagnosis of Pacemaker Failure to Output

Abstract: In a routine monitor electrocardiogram few hours after implantation of a dual-chamber pacemaker, there was a suspicion of ventricular oversensing leading to failure to output. Pulse oximeter plethysmographic wave signal virtually excluded this suspicion. This case report demonstrates the clinical utility of initial pulse oximeter wave analysis in excluding pacemaker failure to output.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…6,14,15 Our work also showed that clinicians rely on pulse palpation when ECG interpretation is difficult, despite its known limitations 16,17 which are accentuated in TCP due to the pseudopulsatile flow generated by skeletal muscle contractions. 18 Potential solutions include using pulse oximetry waveform, [19][20][21] end-tidal capnography, 22,23 doppler, 16 or point-of-care-ultrasound. 24 We favor point-of-care-ultrasound as a gold standard due to established feasibility (Figure 2).…”
Section: Atrial Fibrillationmentioning
confidence: 99%
“…6,14,15 Our work also showed that clinicians rely on pulse palpation when ECG interpretation is difficult, despite its known limitations 16,17 which are accentuated in TCP due to the pseudopulsatile flow generated by skeletal muscle contractions. 18 Potential solutions include using pulse oximetry waveform, [19][20][21] end-tidal capnography, 22,23 doppler, 16 or point-of-care-ultrasound. 24 We favor point-of-care-ultrasound as a gold standard due to established feasibility (Figure 2).…”
Section: Atrial Fibrillationmentioning
confidence: 99%